Feminism in Samira Ahmed’s Interment - Elok Naqiyyah Salsabila; Asep Abbas Abdullah; Endratno Pilih Swasono; Haris Shofiyuddin; Abu Fanani (Program Studi Pendidikan Bahasa Inggris, Universitas Pendidikan Muhammadiyah Sorong, 2026)
This study is about women’s efforts to get justice because their life, their habit as well as their existence as Muslim minority in non-Muslim majority are not well-fulfilled in Samira Ahmed’s Interment. The researcher, then, focuses on why the main character strives and how the main character strives for her race. Using feminism theory and qualitative descriptive and dramatic method, the study finds how courageous the women in fighting their rights as Muslims living in non-Muslim democratic country, USA, taking pain to get their rights as citizen whose religious life is guaranteed by the country’s law by using the following strategy of struggle such as her intellect consisting of being herself and realizing themselves as female Muslim.